Analisis Implementasi Strategi Bauran Pemasaran 7P pada Usaha Tempe Mendoan - Anisa Anugra Heny; Rizal Wahyu Pratama (RESWARA: Jurnal Riset Ilmu Teknik, 2023)
This study aims to analyze the implementation of the 7P marketing mix strategy in tempe mendoan businesses as a form of traditional culinary micro-enterprise in Indonesia. Increasing competition in the culinary sector and changes in consumer preferences require micro and small business actors to apply appropriate marketing strategies to ensure business sustainability. This research employs a qualitative descriptive approach with data collected through in-depth interviews, direct observation, and documentation. The research informants consisted of business owners, employees, and consumers of tempe mendoan. Data analysis was conducted using the interactive analysis model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results indicate that the product element focuses on maintaining taste consistency and product freshness, while pricing strategies are set at affordable and competitive levels. Distribution is mainly conducted through direct sales and local markets, supported by promotional activities dominated by word-of-mouth and limited use of social media. The people element plays an important role in maintaining service quality, although service processes have not been formally standardized. Physical evidence, such as cleanliness of the business location and product appearance, also influences consumer perceptions. Overall, the implementation of the 7P marketing mix strategy contributes positively to customer satisfaction and the sustainability of tempe mendoan businesses; however, improvements are still needed in promotional innovation and process standardization.